Tourism Initiatives as a Lever for Reintegration of Former FARC Combatants in Colombia - Anne Marie Van Broeck; Monica Guasca; Dominique Vanneste (Via@, 2019)
Within the framework of the peace agreement signed between the Colombian government and the Revolutionary Armed Forces of Colombia (FARC-EP) - the largest and oldest guerrilla group in the country – twenty-four Territorial Training and Reincorporation Spaces (known by the Spanish acronym ETCR) were created to temporarily house ex-combatants and to give them a space to set up productive projects as part of their reintegration process. Ex-combatants have opted for projects related to goods production (e.g., agriculture, textile, pisciculture, etc.). Some have also considered tourism as an attractive entrepreneurial path.The paper offers an overview of tourism-related initiatives undertaken by ex-combatants from the different ETCRs by performing content analysis on more than 100 online publications pertaining to the initiatives. This was complemented with semi-structured interviews with people involved in the tourism projects or who visited the ETCR. The intention is to provide a first inventory of the existence of these projects, their present situation and the difficulties they encounter. The article initiates an assessment of their potential and feasibility in the future, and seeks to open up a research agenda for tourism as a reintegration strategy.